Numerical heat transfer modeling and climate adaptation analysis of vacuum-photovoltaic glazing. (15th April 2022) - Tan, Yutong; Peng, Jinqing; Luo, Yimo; Luo, Zhengyi; Curcija, Charlie; Fang, Yueping
Highlights: Numerical model for a four-layer CdTe-based VPV glazing was developed. The model was validated experimentally with a U-value of 0.92 W/(m 2 ⋅K). About 60% heat loss and heat gain can be reduced by VPV in cold and hot climates. More than 40 kWh/m 2 average power generation of VPV windows can be achieved. Abstract: Vacuum-photovoltaic (VPV) glazing has attracted much attention due to its excellent thermal insulation performance and its ability to utilize solar energy. However, few simulation models have been established based on actual products and rarely have been validated by experiments. In this paper, a four-layer CdTe-based VPV glazing was developed and the corresponding numerical heat transfer model was established with the integration of a dynamic power generation model. The numerical model was then validated against both the results from the WINDOW program and a guarded hot box experiment. Afterward, the validated model was employed to analyze the energy and power generation performance of the VPV glazing in diverse climate zones in China with Harbin, Beijing, Changsha, Guangzhou, and Kunming used as representative cities. The numerical simulation results indicate that the U-value of the proposed VPV glazing is 0.89 W/(m 2 ⋅K), which is in good agreement with the experimental results. Compared with a normal double glazing, the average energy reductions achieved with VPV glazing in air conditioning seasons are 128 kWh/m 2, 23 kWh/m 2, 45 kWh/m 2, and 52 kWh/m 2 in Harbin, Beijing, Changsha, and Guangzhou, respectively. In addition, the average annual power outputs of VPV glazing in Harbin, Beijing, Changsha, Guangzhou, and Kunming are 47 kWh/m 2, 48 kWh/m 2, 34 kWh/m 2, 36 kWh/m 2, and 45 kWh/m 2, respectively. The numerical model developed in this study can be used for energy-saving potential analysis and optimization of VPV glazing in different meteorological conditions, the results of which could provide guidance for the effective application of VPV glazing.